Gregory Baum’s “Effervescent” Hope in the Church: Some reflections on the inclusivity of Gregory Baum’s ecumenism and their bearing on the Church of the Future - Kirkpatrick, Patricia (Théologiques, 2021)
This essay explores the importance of dialogue in ecumenical relations in the thought and writing of Gregory Baum. To do so it focusses on three of his writings. The first is an interview he gave in 2005 to A. miller in the Journal of Philosophy and scripture. The second is his discussion of ecumenism in his 2005 book Amazing Church. A Catholic Theologian Remembers a Half Century of Change. The third is one of the last writings of Gregory Baum written in 2016 entitled « Interreligious Dialogue Includes Listening to Secular Voices », in the Toronto Journal of Theology. All three of these writings stem from his earlier writing on the second Vatican Council. The three documents which are referred to are Unitatis redintegratio, Nostra aetate, and Gaudium et spes as well as the 1991 document Dialogue and Proclamation. The essay therefore explores Baum’s appreciation of all three forms of ecumenical dialogue, namely that which exists between Christian denominations, inter faith and dialogue with secular thought. These are not exhaustive commentaries on the previous documents and they are certainly not exhaustive in terms of Baum’s theological perspective on ecumenical dialogue. Rather, they will serve as a springboard when asking if his perspectives are still relevant for the church today.